The effect of simulated problem learning in nursing ethics on moral sensitivity, empathy and critical thinking of nursing students: A quasi-experimental study - Qu, Zhifei; Sun, Jingjing; Li, Li; Zhao, Lijing; Jiang, Nan; Fan, Jia; Zhang, Jiaxin; Liang, Bing (Nurse education in practice, 2024)
Compare the effects of Simulation with problem-based learning (SPBL) and Problem-based learning (PBL) in nursing ethics education on nursing students’ moral sensitivity, empathy, critical thinking, test scores and teaching satisfaction. Promoting nursing students’ individual and ethical and abilities through education is an essential way to improve their ethical performance and build trustful relationship with patients. Despite significant efforts in this area, few have evaluated the effectiveness of Simulation with problem-based learning and Problem-based learning as applied to nursing ethics education. A quasi-experimental design based on a non-equivalent control group pre-test/post-test. A quasi-experimental design was used. Participants were 161 undergraduate nursing students from two levels of a university, 88 subjects in the experimental group were taught using Simulation with problem-based learning and 73 subjects in the control group were taught using Problem-based learning. A pre-test, post-test and questionnaire were used to assess the effectiveness of student nursing ethics education. χ2 test was used to examine group differences in students’ characteristics and satisfaction with teaching post-intervention. Student’s t-test was used to assess group differences in scale scores and test scores. Compared to the pre-test, empathy as well as critical thinking were significantly higher in the PBL group (P<0.05), but there was no significant change in moral sensitivity (P>0.05); moral sensitivity, empathy and critical thinking were significantly higher in the SPBL group (P<0.05). Moreover, this study also showed that improvement in moral sensitivity, empathy, critical thinking and grades was more significant in the SPBL group of nursing students compared to the PBL group (P<0.05) and no statistically significant difference was found between the two groups in terms of teaching satisfaction (P>0.05). The use of Simulation with problem-based learning in nursing ethics education has a positive impact on nursing students' competency development and knowledge acquisition. Nurse educators should consider this teaching method and promote change to increase the effectiveness of nursing ethics education. •Nursing ethics education plays a vital role in developing nursing students' ability to solve practical clinical problems.•Problem-based learning instruction is limited in terms of interactive and contextualized learning experiences.•Simulation with problem-based learning can improve nursing students' moral sensitivity, empathy, and critical thinking more effectively than problem-based learning.•Our findings suggest that simulation with problem-based learning should be promoted for use as part of the nursing ethics education program design.